ANALYSIS OF MORPHOLOGICAL RESULTS OF KIDNEYS OF OFFSPRING OBTAINED UNDER CONDITIONS OF EXPERIMENTAL DIABETES - Mamadaliyeva Odinabonu; Tilyabov Ikrom (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In the world, among endocrine diseases, diabetes mellitus and its consequences, kidney pathologies occupy the highest place in prevalence. According to the World Health Organization (WHO), "... studies in Australia, Europe, Central Asia, the Middle East and North America show that the prevalence of kidney diseases among the population is 10-45%, with an average level of 26% ..." [WHO data 2022, https://www.who.org]. At the same time, the development of modern diagnostic capabilities in the diagnosis of the disease in order to avoid a negative impact on people's lives, the occurrence of various conditions leading to an increase in the disease, leads to morphological and functional changes in the subtractive system.